2019
DOI: 10.1002/celc.201901628
|View full text |Cite
|
Sign up to set email alerts
|

Photosystem I Multilayers within Porous Indium Tin Oxide Cathodes Enhance Mediated Electron Transfer

Abstract: Understanding and improving charge transfer pathways between extracted Photosystem I (PSI) protein complexes and electrodes is necessary for the development of low‐cost PSI‐based devices for energy conversion. We incorporated PSI multilayers within porous indium tin oxide (ITO) electrodes and observed a greater mediated photocurrent in comparison to multilayers on planar ITO. First, the mediated electron transfer (MET) pathway in the presence of 2,6‐dichlorophenolindophenol (DCPIP) and ascorbate (AscH) was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…For example, the theoretical current capacity of biophotovoltaic cells containing cyanobacteria is postulated to range in the orders of 0.07-0.77 mW cm −2 whereas their empirical values typically average in the 0.0001-0.01 mW cm −2 range [6,40]. Technological advances in terms of improving anode design and cell architecture to implement better photosynthetic entity binding, film loading, increased electroactive surface area, mass transport capabilities and light transmittance have been reported [19,[41][42][43]. On the other hand, redox mediation for long-range EET in semiartificial photosynthetic systems (E-MET), can be broadly classified into two, namely; exogenous diffusible redox mediators (Fig.…”
Section: Improving the Electric Contact At The Photosynthetic Entity-electrode Interfacementioning
confidence: 99%
See 2 more Smart Citations
“…For example, the theoretical current capacity of biophotovoltaic cells containing cyanobacteria is postulated to range in the orders of 0.07-0.77 mW cm −2 whereas their empirical values typically average in the 0.0001-0.01 mW cm −2 range [6,40]. Technological advances in terms of improving anode design and cell architecture to implement better photosynthetic entity binding, film loading, increased electroactive surface area, mass transport capabilities and light transmittance have been reported [19,[41][42][43]. On the other hand, redox mediation for long-range EET in semiartificial photosynthetic systems (E-MET), can be broadly classified into two, namely; exogenous diffusible redox mediators (Fig.…”
Section: Improving the Electric Contact At The Photosynthetic Entity-electrode Interfacementioning
confidence: 99%
“…4) [65]. The paired system is utilized since DCPIPH 2 , obtained after ascorbic acid oxidation and two-proton-two-electron transfer to DCPIP, is an efficient electron donor for the P 700 + redox active center [43,66]. Comparatively, ascorbate alone is a poorly efficient electron donor for P 700 + , even at high concentrations [67][68][69].…”
Section: Dcpipmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of pore size was studied by comparing photocurrents between mesoporous (20-100 nm) and macroporous (5 µm) electrodes using 2,6-dichlorophenolindophenol (DCPIP) and ascorbate as redox mediator for PSI. The macroporous electrode showed three times higher photocurrent than the mesoporous electrode [96]. The authors observed that the macroporous electrode increased the active surface area twice compared to the mesoporous electrode with the same PSI mass loading.…”
Section: Multi-layer Assembly Multilayered Lipid Membrane Stacks 3dmentioning
confidence: 97%
“…PSI is known to improve the photoelectrochemical performance of many electrode materials under various conditions. Photoelectrochemical investigations of PSI have commonly used a three-electrode liquid cell to enable a focused study of the photoelectrochemical interface between PSI and a single electrode. ,, In contrast, fewer researchers have reported the use of PSI in a two-electrode solar cell, and most of these include solid-state devices. ,, Solid-state devices with PSI depend on direct electron transfer from electrodes or conducting materials to and from the P 700 and F B sites, which complicates device fabrication in comparison to devices dependent on mediated electron transfer (MET). Alternatively, liquid cells rely on MET, in which redox reactions occur throughout a protein film as reactants freely diffuse to the electrodes …”
Section: Introductionmentioning
confidence: 99%